Integrative Transcriptomic Analysis Reveals Upregulated Apoptotic Signaling in Wound-Healing Pathway in Rat Liver Fibrosis Models - Jihyun Kim; Changyong Lee; Sang Gyun Noh; Seungwoo Kim; Hae Young Chung; Haeseung Lee; Jeon-Ok Moon (MDPI AG, 2023)
Liver fibrosis, defined by the aberrant accumulation of extracellular matrix proteins in liver tissue due to chronic inflammation, represents a pressing global health issue. In this study, we investigated the transcriptomic signatures of three independent liver fibrosis models induced by bile duct ligation, carbon tetrachloride, and dimethylnitrosamine (DMN) to unravel the pathological mechanisms underlying hepatic fibrosis. We observed significant changes in gene expression linked to key characteristics of liver fibrosis, with a distinctive correlation to the burn-wound-healing pathway. Building on these transcriptomic insights, we further probed the p53 signaling pathways within the DMN-induced rat liver fibrosis model, utilizing western blot analysis. We observed a pronounced elevation in p53 protein levels and heightened ratios of BAX/BCL2, cleaved/pro-CASPASE-3, and cleaved/full length-PARP in the livers of DMN-exposed rats. Furthermore, we discovered that orally administering oligonol-a polyphenol, derived from lychee, with anti-oxidative properties-effectively countered the overexpressions of pivotal apoptotic genes within these fibrotic models. In conclusion, our findings offer an in-depth understanding of the molecular alterations contributing to liver fibrosis, spotlighting the essential role of the apoptosis pathway tied to the burn-wound-healing process. Most importantly, our research proposes that regulating this pathway, specifically the balance of apoptosis, could serve as a potential therapeutic approach for treating liver fibrosis.